Fusobacterium necrophorum in an Abdominal Aortic Aneurysm, Treated by Once Daily Ertapenem - Wotherspoon, D.; Street, J. A.; Hedderwick, S.; Baker, R. (International Journal of Angiology, 2012)
Inflammatory aneurysms may make up a small percentage of the total number of abdominal aortic aneurysms, but they present their own unique challenges. We present a case of a 65-year-old man whose aneurysm was found to be colonized by Fusobacterium necrophorum.
Keywords: abdominal aortic aneurysm; aneurysm; C-reactive protein; infection; mycotic aneurysm; risk factors; repair